Upaya KUA dalam Mengurangi Tingkat Perceraian Pasangan Perkawinan Di Bawah Umur - M. Khoirudin Romadhoni (HOKI : Journal of Islamic Family Law, 2024)
The background of this research is the high rate of divorce for underage couples in KUA, Sekaran District, Lamongan Regency. So that researchers are interested in knowing what factors are the cause of divorce in underage couples and what efforts have been made by the KUA of Sekaran District, Lamongan Regency to reduce the number of divorces in underage married couples. The type of research used by researchers is empirical juridical research, which uses data collection techniques through observation, interviews and documentation. The data collected by the authors, then analyzed through the process of data reduction, data presentation and drawing conclusions. The results of the study showed that there was a synchronization of problems that were resolved by the KUA of Sekaran District, Lamongan Regency, but they were divorced due to economic problems, infidelity and communication. Therefore KUA provides space and time for consultation as a form of coaching or assistance. The efforts of the KUA in Sekaran District, Lamongan Regency are efforts to foster and assist marriage, and Marriage Socialization from the KUA in Sekaran District in collaboration with the Lamongan BPKBN which aims to provide understanding to the community about the purpose of marriage, the age limit for marriage, carrying out marriages according to the provisions (Islamic law, overcoming conflicts in the household, and what are the responsibilities of husband and wife in the household. Meanwhile, the KUA has currently made efforts since 2020 until now. This effort has been running for 3 years and has had a positive impact on reducing the divorce rate for underage couples in 2022 in Sekaran District, Lamongan Regency.